Pengaruh Brand Ambassador, Brand Image, Electronic Word Of Mouth (E-WOM) Terhadap Keputusan Pembelian Produk Nature Republic Pada Marketplace Shopee - Patricia Dias Riandari (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2023)
This study aims to determine the effect of Brand Ambassador, Brand Image, Electronic Word of Mouth on Purchase Decisions for Nature Republic Products on the Shopee Marketplace. The sampling method in this study is non-probability sampling with purposive sampling. The research method used in this study was a quantitative survey with a sample of 58 people. The population used in this study were women or men who used Nature Republic products. The analysis used used SPSS 26. The research data analysis technique used multiple linear regression analysis, t test, F test and the coefficient of determination (R2). The data collection process was carried out by distributing google form questionnaires. The results of this study indicate that brand ambassadors have a significant effect on purchasing decisions as evidenced by the existence of a T-test value of 0.860 at a significance level of 0.05. Brand image has a significant effect on purchasing decisions of 0.779 with a significance level of 0.05. In addition, E-wom also has a significant effect on purchasing decisions of 0.662 with a significance level of 0.05. The F-test table was created to measure the effect of the independent variables simultaneously and the F-test statistical value was 0.129 which was greater than the significance level of 0.05, so it could be concluded that the F-test table had no effect. on purchasing decisions. From the findings above, it can be concluded that Brand Ambassador and Brand Image have a positive effect on purchasing decisions, while E-wom has no significant effect on purchasing decisions.